On a collection of deep-water shrimp (Crustacea, Decapoda) from the Dutch Caribbean, with the description of a new species of Pseudocoutierea - Olthof, Gabriël; Becking, Leontine E.; Fransen, Charles H.j.m. (Zootaxa, 2018)
A collection of shrimp from deep reefs in the Dutch Caribbean is described. Most material originates from the Bonaire deep reef expedition (2013) by Wageningen Marine Research of Wageningen University. Some additional material was available from dives on Curaçao (2014). A new species of Pseudocoutierea Holthuis was recognized in the material collected off Bonaire. The new species is described and illustrated and its position in the phylogeny of the genus Pseudocoutierea analyzed. A key to the species in the genus is presented.